Telehealth As An Alternative Method For Improving Anti-Retroviral Treatment Compliance In Adolescent And Young Adults With Hiv: A Scoping Review - Artanti Lathifah; Ahmad Ihsan Fathurrizki; Hesti Platini; Ayyida Aini Rahmah (Universitas Padjadjaran, 2022)
Compliance of patients with human immunodeficiency virus (HIV) in undergoing therapy is essential in reducing the viral load. Currently, the world is in the era of revolution 4.0, where there is a combination between technology and human needs. The effort to adapt to this condition is by utilizing Telehealth. Telehealth is considered efficient in controlling, monitoring, and providing palliative care remotely. This study's purpose is to review Telehealth's effectiveness as an alternative method of increasing anti-retroviral treatment compliance in children, adolescents, and young adults with HIV. Using scoping review method with inclusion criteria for articles published in 2012 – 2022, Randomized Control Trial and Experimental Study research design, and published in English. Selection of articles using PRISMA Flow Diagram. The database consists of PubMed and EBSCO using keywords telenursing, compliance, anti-retroviral agents, and children. Four articles were included in the study out of 895 identified articles. The use of Telehealth provides the potential for both children and youth to increase patient motivation and adherence to treatment. Telehealth in patients with HIV used short messages. So, Telehealth has the potential to become an alternative method of increasing anti-retroviral treatment adherence in children, adolescents, and young adults with HIV.